2015
DOI: 10.1158/2326-6066.cir-15-0099-t
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Targeting of FcγRs and FcαRI Enhances Tumor Cell Killing

Abstract: Efficacy of anticancer monoclonal antibodies (mAb) is limited by the exhaustion of effector mechanisms. IgG mAbs mediate cellular effector functions through FcgRs expressed on effector cells. IgA mAbs can also induce efficient tumor killing both in vitro and in vivo. IgA mAbs recruit FcaRI-expressing effector cells and therefore initiate different effector mechanisms in vivo compared with IgG. Here, we studied killing of tumor cells coexpressing EGFR and HER2 by the IgG mAbs cetuximab and trastuzumab and their… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…To further improve ADCP activity, the Fc region of tumor-targeted antibodies could be engineered to increase its interaction with activatory Fc receptors, most importantly FcγRIIa, on macrophages [95]. While development of clinical antibodies is primarily focused on IgG, therapeutic potentials of other Ig isotypes (IgA and IgE) are being investigated in several pre-clinical studies where monocytes/macrophages are also important in effecting the ADCC/ADCP functions [96][97]. …”
Section: Pharmacological Modulation Of Macrophages/tamsmentioning
confidence: 99%
“…To further improve ADCP activity, the Fc region of tumor-targeted antibodies could be engineered to increase its interaction with activatory Fc receptors, most importantly FcγRIIa, on macrophages [95]. While development of clinical antibodies is primarily focused on IgG, therapeutic potentials of other Ig isotypes (IgA and IgE) are being investigated in several pre-clinical studies where monocytes/macrophages are also important in effecting the ADCC/ADCP functions [96][97]. …”
Section: Pharmacological Modulation Of Macrophages/tamsmentioning
confidence: 99%
“…IgA2 EGFR was more effective than cetuximab in vivo against EGFR-transfected Ba/F3 target cells [ 221 ]. Very recently, it was also shown that the combination of IgG and IgA mAbs to two different tumor targets (EGFR and HER2) led to enhanced cytotoxicity compared with each isotype alone [ 222 ].…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…When comparing neutrophil‐mediated ADCC through either FcγRs or FcαRI, it was found that FcαRI is the most effective FcR in triggering ADCC and inducing migration of neutrophils into tumor colonies . Interestingly, a recent article described the use of a combination of both IgG and IgA mAbs in the targeting of two different tumor antigens, EGFR and Her2/Neu, on A431 cells in a xenograft tumor model in mice, leading to increased cytotoxicity compared to each isotype alone . The use of IgA mAbs furthermore could create opportunities for treatment of specific types of cancers, for instance B‐cell lymphomas, in which IgG‐mediated treatments have been previously found less effective.…”
Section: The Role Of Neutrophils In Antibody Therapy Against Cancermentioning
confidence: 99%